2016
DOI: 10.3892/ijmm.2016.2803
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences in osteogenic differentiation potency in the thoracic ossification of the ligamentum flavum under cyclic mechanical stress

Abstract: Mechanical stress and genetic factors play important roles in the occurrence of thoracic ossification of ligament flavum (TOLF), which can occur at one, two, or multiple levels of the spine. It is unclear whether single- and multiple-level TOLF differ in terms of osteogenic differentiation potency and osteogenesis-related gene expression under cyclic mechanical stress. This was addressed in the present study using patients with non-TOLF and single- and multiple-level TOLF (n=8 per group). Primary ligament cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…Due to the progressive nature of the ossification and the refractoriness to conservative treatment, TOLF generally requires aggressive surgical intervention[14]. Several investigations suggested that potential contributing factors associated with TOLF, such as mechanical effects[57], inflammatory factors [8, 9]and genetic factors[10, 11], but the underlying mechanism of TOLF has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the progressive nature of the ossification and the refractoriness to conservative treatment, TOLF generally requires aggressive surgical intervention[14]. Several investigations suggested that potential contributing factors associated with TOLF, such as mechanical effects[57], inflammatory factors [8, 9]and genetic factors[10, 11], but the underlying mechanism of TOLF has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been demonstrated that ciRS-7 can repress Alzheimer’s disease (AD) development by suppressing NF-κB protein synthesis and inducing its cytoplasmic localization, promoting UCHL1 expression and UCHL1-induced amyloid precursor protein (APP) and BACE1 ubiquitination and degradation 13 . Moreover, primary ligament cells were preferentially used for transcription profiling in most OLF research 42, 43. In this study, for the first time, we used normal and ossified ligament tissues for transcription profiling, which reflect more closely the change in expression of ncRNAs and mRNA of OLF in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of OLF remains to be elucidated, abnormal expression of osteogenic differentiation and cell proliferation related genes in LF cells may serve important roles (8). The mRNA levels of osteogenic markers [alkaline phosphatase (ALP), runt-related transcription factor 2, osterix and osteopontin)] in addition to signaling pathway genes [bone morphogenetic proteins (BMPs), Wnt/β-catenin and Notch] (9,10), were identified to be higher in patients with OLF compared with non-OLF subjects. Recombinant BMP2 or BMP14 [also known as growth/differentiation factor (GDF) 5] modification induced the osteoblastic differentiation of LF cells and promoted bone nodule formation, finally triggering neurological impairment in rat models (11,12), while downregulation of Notch2 ameliorated the processes (10).…”
Section: Introductionmentioning
confidence: 99%